2018
DOI: 10.1108/jmd-06-2017-0213
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and leadership flexibility

Abstract: Purpose-In a context of great complexity, many authors have focused on the beneficial effects of leadership flexibility (Denison et al., 1995), a capacity theoretically associated with mindfulness. The purpose of this paper is to better understand the relationship between mindfulness and behavioral flexibility in leaders. Design/methodology/approach-Data were collected from two samples: 100 active leaders from diverse economic sectors and 62 students pursuing an executive MBA degree. Findings-The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 42 publications
2
50
0
1
Order By: Relevance
“…However, contrary to the suggestions that mindfulness turns employees into uncritical drones and promotes passive acceptance of organizational dictates, Baer (2015) argues that mindfulness is in fact more likely to promote proactive, engaged behavior. Preliminary research supports this latter view, providing evidence that mindfulness encourages adaptive, flexible responding (Baron et al, 2018;Carmody et al, 2009), and makes employees more sensitive to mistreatment (Walsh & Arnold, 2020).…”
Section: Balance As Tempered Viewmentioning
confidence: 78%
“…However, contrary to the suggestions that mindfulness turns employees into uncritical drones and promotes passive acceptance of organizational dictates, Baer (2015) argues that mindfulness is in fact more likely to promote proactive, engaged behavior. Preliminary research supports this latter view, providing evidence that mindfulness encourages adaptive, flexible responding (Baron et al, 2018;Carmody et al, 2009), and makes employees more sensitive to mistreatment (Walsh & Arnold, 2020).…”
Section: Balance As Tempered Viewmentioning
confidence: 78%
“…Relatedly, research indicated that leader mindfulness is associated with increases in a well-sought leader characteristic in these changing times: leader flexibility (Baron et al 2018). Flexibility according to the authors pertains two opposing dimensions that represent different tensions within organizations: (1) the integration of performance goals and human relationships (i.e., self-assertive and directive vs collaborative and supportive) and (2) the tendency to be directed toward the external context or in-house procedures (i.e., long-term strategy vs short-term execution).…”
Section: Leader Outcomesmentioning
confidence: 99%
“…Simply put, it is, "a mental state achieved by focusing one's awareness on the present moment, while calmly acknowledging and nonjudgmentally accepting feelings and thoughts" (Sanyal & Rigg, 2020, p. 2). While much of the research on it is theoretical in nature, there are studies linking it to positive leadership outcomes including mental health (Roche et al, 2014), employee wellbeing, effectiveness (Reb et al, 2014) and leader flexibility (Baron et. al.…”
Section: A Framework For Becoming An Emotionally Adaptable Leader (Eal)mentioning
confidence: 99%